Design and Development of MY DASS; A Mental Health Application for Malaysia Secondary School Students - CHAI, XIAO HUI; WAHID, NORFARADILLA (Applied Information Technology And Computer Science, 2024)
MY DASS is a comprehensive mental health application proposed to address the problem of difficulty managing a large number of manual test results from students and not accurate online tests, the proposed application includes the Depression Anxiety Stress Scale (DASS), Instrument PHQ-9, and Instrument GAD-7 to be conducted among secondary school students. The methodology technique chosen for the development of this project is the Prototype model. MY DASS is developed for two platforms, i.e., mobile and web-based platforms; where the first is meant for school students and parents, while the second is for school counselors and administrators. The implementation of the Android mobile application is done using Android Studio and Firebase while the web application is done using Visual Studio Code and Firebase. Based on the results of the testing phase, the application is effective in solving problems faced by secondary school students, parents, and school counselors.